Mechanical properties of different airway stents. Issue 4 (April 2015) - Ratnovsky, Anat; Regev, Noa; Wald, Shaily; Kramer, Mordechai; Naftali, Sara
Highlights Numerical simulations and mechanical measurement were carried out to compare the mechanical properties of different airway stents within three trachea models. Correlation was observed between the diameter of the stent and the stress distribution on the trachea. Stents made of the same material(s) exerted different stresses due to differences in their structure. Stenosis significantly increases stress levels in all stents.